2011
DOI: 10.1063/1.3627444
|View full text |Cite
|
Sign up to set email alerts
|

High spectral resolution, real-time, Raman spectroscopy in shock compression experiments

Abstract: The use of Raman measurements to examine molecular changes associated with shock-induced structural and chemical changes in condensed materials often poses two challenging requirements: high spectral resolution and significantly reduced background light. Here, we describe an experimental method that addresses these requirements and provides better quality data than the time resolved approach used previously. Representative measurements are presented for shock compression of two energetic crystals: pentaerythri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…There have been several attempts at measuring the shock-driven chemistry of benzene using optical techniques 1 , 15 , 21 23 . Yakusheva et al observed optical absorbance changes 300 ns behind the shock front above ~13.5 GPa 24 .…”
Section: Introductionmentioning
confidence: 99%
“…There have been several attempts at measuring the shock-driven chemistry of benzene using optical techniques 1 , 15 , 21 23 . Yakusheva et al observed optical absorbance changes 300 ns behind the shock front above ~13.5 GPa 24 .…”
Section: Introductionmentioning
confidence: 99%
“…The second trigger signal was generated from the emission of an aluminium/quartz interface. Because the emission space was in the middle of the target, this kind of trigger method could largely improve the experimental precision compared with the electric trigger pin reported by Hemmi et al [16] The first signal provides the desired time separation to achieve the optimal laser output. In addition, the 𝑄-switch signal was firstly sent to the pyrometer and converted into electric signal by the pyrometer, then it arrives at the detection system with a controlled time delay to synchronize the time window of the gated intensifier with the laser pulse.…”
mentioning
confidence: 99%